The Role of Lubrication Mechanisms in the Knee Synovial Joints - Ali, Aseel Mohammed; Yousif, Albert E. (Nahrain University College of Engineering Journal, 2008)
Synovial joints form the most important feature of the human body as they represent the centers of the most essential and basic activity in the human beings, which is motion. Starting from the role that are played by the lubrication regimes in effectiveness and maintenance of the joint this study was initiated. It investigates the lubrication systems that are operative in synovial joint. Depending on the loading conditions and sliding velocity during one gate of the walking cycle the profile of the synovial film thickness and the pressure developed in the knee joint when the hydrodynamic and elastohydrodynamic lubrication regimes are operative was determined. For the hydrodynamic and elastohydrodynamic lubrication analysis a mathematical model obtained by solving the governing equation using numerical methods. Results showed that for the hydrodynamic action the minimum film thickness determined was between (0.365-1.8) ?m and the pressure developed ranged between (20.6-860.449) kN/m2. While for elastohydrodynamic action the minimum film thickness ranged from (2.5-3.57) ?m and the developed pressure ranged between (97.68- 146.5) kN/m2. Finally, it was shown that in specific conditions hydrodynamic and elastohydrodynamic lubrication mechanisms gave a good explanation to how the joint functions